PSYCHOLOGY OF HANDICAPPED PEOPLE AND THEIR BEHAVIOR - Bhavna Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
A significant number of professionals from all walks of life throughout the globe are dedicating their careers to the field of rehabilitation. They go to tremendous lengths in order to facilitate the integration of the handicapped individual or kid into regular society. and the course of everyday life. There are moments when all of their hard work pays off in a big way. The majority of the time, the extent of one's achievement is constrained by factors that are not fully understood.